The Impact of Sales Promotion, User Interface and User Experience Design on Shopee App Users’ Repurchase Intentions - Tobing, Gulielmus Brahma Rantau Lumban; Adinata, Patrick Vivid; Pranatasari, Fransisca Desiana; Kristia, Kristia (International Journal of Engineering and Management Sciences, 2023)
By 2022, Gen Z and millennial consumers dominated Shopee usage in Indonesia. Similar e-commerce platforms are forced to constantly innovate to remain competitive in the market due to increasing competition. Therefore, the primary focus of e-commerce platform development should be on the user interface, user experience design, and promotions that are appealing and easy to access so that potential customers are inclined to repurchase. This research aims to determine the influence of UI design, UX design, and promotions on the repurchase intention of users of the Shopee application. The sampling method used was systematic sampling. Ninety-six respondents are included in the sample. This study uses descriptive analysis, classical assumption tests, multiple linear regression, and hypothesis testing for data analysis. SPSS Statistics 28.0 was used for data processing. The study found that user interface design, user experience design, and sales promotions statistically impact the repurchase intention of users of the Shopee application. The results demonstrate the effectiveness of repurchase intent in e-commerce.